Está en la página 1de 5

Grfica

Ecuacin

X= 4cos(t) - cos (4t)


Y= 4sen(t) - sen(4t)

X= 9cos(t) - cos(9t)
Y=9sen(t) - sen(9t)

X=13cos(t) cos(13t)
Y=13sen(t) sen(13t)

X=6cos(t) + cos(6t)
Y= 6sen(t) + sen6(t)

X=15cos(t) + cos15(t)
Y=15sen(t) + sen15(t)

(-5,-8)

X=8cos(t)-5
Y=8sen(t)-8

X= 9cos(t) - 9
Y=16sen(t)+ 4

X= 9cos(t) +3
Y = 9sen(t) -1

X= 4 cos(t)-2
Y= sen(t) +3

X=4sen(t)-cos(4t)
Y= 4cos(t)-sen(4t)

X=6sen (t)-cos(6t)
Y=6cos(t)-sen (6t)

X=8sen (t)-cos(8t)
Y=8cos(t)-sen (8t)

X=12sen (t)-cos(12t)
Y=12cos(t)-sen (12t)

X=16sen (t)-cos(16t)
Y=16cos(t)-sen (16t)

X= 5sen(2t)
Y= 3sen(t)

X= 9sen(2t)
Y= 10sen(t)

X= 4sen(2t)
Y= 9sen(t)

X= 2sen(2t)
Y= 12sen(t)

X= 15sen(2t)
Y= 6sen(t)

X=2(6)cos(t)-6sen(2t)
Y=3sen(t)

X=2(3)cos(t)-sen(3t)
Y=5sen(t)

X=2(5)cos(t)-sen(5t)
Y=3sen(t)

X=2(9)cos(t)-sen(9t)
Y=27sen(t)

X=2(3)cos(t)-sen(3t)
Y=27sen(t)

R= x2 + y2 -4=0

R=(x-4)2 y2-9